Transformasi Strategi Perencanaan Sumber Daya Manusia (SDM) dalam Menghadapi Disrupsi Era Digital - Putri Handayani; Melda Haulia; Rully Yacob; Daniel Octavianus (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze adaptive Human Resource (HR) planning strategies in addressing the challenges of the digital era, characterized by the rapid advancement of information and communication technology, including automation, Artificial Intelligence (AI), and remote work trends. This research employs a qualitative literature review approach to explore the paradigm shift from traditional HR management toward Digital Human Resource Management (Digital HRM). The findings indicate that HR planning strategies in the digital age are no longer focused solely on workforce quantity, but instead emphasize the use of People Analytics to predict talent needs and employee turnover, the implementation of reskilling and upskilling to bridge digital competency gaps, and the development of an agile work culture that supports organizational adaptability. The study concludes that organizational success in the digital era depends on the ability of management to align technological strategies with human potential development, where effective HR planning must balance technological efficiency with a human-centered approach to achieve sustainable competitive advantage.